Application of 30 Degree Head Up Position in Non-Hemorrhagic Stroke Patients in Improving Oxygen Saturation in the Stroke Unit Room of the Gunung Jati Hospital Cirebon - Syaripudin, Ahmad; Herlina; Pujiyana; Okta, Ira Rahayu; Hidayat, Lalu Rahmatullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Stroke is a cerebrovascular disease that can occur suddenly and is an emergency condition, this is due to blockage of blood vessels in the brain, resulting in a lack of oxygen supply in the blood, to the brain. The purpose of the study was to determine the effect of the head up position of 30 degrees on increasing oxygen saturation in stroke patients. The method uses a qualitative approach with case studies as the main method. Data collected through interviews, documentation, data analysis up to the provision of intervention and evaluation. The research was conducted in the Stroke Unit Room of Gunung Jati Hospital, Cirebon City in March 2024. The sample in this study was one patient with stroke, with the provision of 30 degree head up intervention carried out for 30 minutes. The results of the study were obtained for 3 consecutive days, namely oxygen saturation experienced significant changes before and after the provision of oxygenation therapy and head up 30 degrees to 98%. In conclusion, the head up position can significantly improve oxygen saturation